2021
DOI: 10.1038/s41598-021-89748-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of spin–orbit-induced magnetic field in GaMnAs by field-scan planar Hall measurements

Abstract: Spin–orbit-induced (SOI) effective magnetic field in GaMnAs film with in-plane magnetic anisotropy has been investigated by planar Hall effect measurements. The presence of SOI field was identified by a shift between planar Hall resistance (PHR) hystereses observed with positive and negative currents. The difference of switching fields occurring between the two current polarities, which is determined by the strength of the SOI field, is shown to depend on the external field direction. In this paper we have dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…It has been shown that, although the injection of spin current is possible from one ferromagnetic layer to another as a result of the action of the planar Hall effect (PHE) [29,30], this mechanism does not lead to the emergence of SOT in a system of two ferromagnetic layers. The planar Hall effect can only cause spin polarization perpendicular to the plane of the sample [31].…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…It has been shown that, although the injection of spin current is possible from one ferromagnetic layer to another as a result of the action of the planar Hall effect (PHE) [29,30], this mechanism does not lead to the emergence of SOT in a system of two ferromagnetic layers. The planar Hall effect can only cause spin polarization perpendicular to the plane of the sample [31].…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…Было показано, что, хотя инжекция спинового тока возможна из одного ферромагнитного слоя в другой в результате действия планарного эффекта Холла (PHE) [29,30], этот механизм не приводит к возникновению SOT в системе из двух ферромагнитных слоев. Планарный эффект Холла способен вызывать лишь спиновую поляризацию, перпендикулярную плоскости образца [31].…”
Section: обсуждение экспериментальных результатовunclassified